Ambulation in labour. Issue 6137 (26th August 1978) - Flynn, A M; Kelly, J; Hollins, G; Lynch, P F
Abstract : In a randomised prospective study of 68 women in spontaneous labour half were allocated to an ambulant group and half to a recumbent group. The duration of labour was significantly shorter, the need for analgesia significantly less, and the incidence of fetal heart abnormalities significantly smaller in the ambulant group than in the recumbent group. Apgar scores at one and five minutes were also significantly greater in the ambulant group. More patients in the recumbent group required augmentations with oxytocic drugs. There was no statistically significant difference in the third stage loss in the two groups. Ambulation in labour should be encouraged: it may bring human benefits while allowing the advantages of hospital supervision.